FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING DIWILAYAH KERJA UPTD PUSKESMAS KAMPAR KABUPATEN KAMPAR - riri maharani; Endang Purnawati Rahayu; Septi Sholehawati (Jurnal Kesehatan Komunitas, 2021)
Stunting is a chronic condition that describes growth retardation due to long-term malnutrition with a threshold (z-score) between -3 elementary school to <-2 elementary school. Based on the results of the 2013 Riskesdas UPTD Kampar Health Center is a Puskesmas that has two villages which are designated as stage II stunting loci, with the prevalence of stunting occurrence 29.4%. The purpose of this study was to determine the factors associated with stunting in the work area of ​​the Kampar UPTD Public Health Center, Kampar district in 2018. This type of research was observational through a quantitative analytic approach with case control design with a sample of 59 stunting mothers and control samples. 59 mother respondents of children under five were not stunting. The data analysis was performed by a computerized system using Univariate and Bivariate analysis with Chi-Square Test. The results showed a relationship between knowledge (P value = 0,000 CI = 5,408-32,065), Parenting Style (P value = 0,039 CI = 1,109-5,005) history of ANC (P value = 0,034 CI = 1,099-4,861) Birth Weight (P value = 0.034 CI = 1,137-5,390), Exclusive breastfeeding (P value = 0,027 CI = 1,169-5,134), immunization history (P value = 0,025 CI = 1,187-5,359), Revenue (P value = 0,002 CI = 1,674-7,753) and family support (P value = 0.020 CI = 1.264-7.458) for the incidence of stunting and no association between history of infectious disease (P value = 1,000 CI = 0.311-2.439) for the incidence of stunting. It is recommended for puskesmas to be able to prepare facilities and infrastructure as a medium in providing counseling and counseling on stunting to the community through posyandu as a place for integrated activities from various sectors.